Stop selling and start leading : how to make extraordinary sales happen - Kouzes, James M., 1945-; Posner, Barry Z.; Calvert, Deb (Wiley, 2018)
"In the Age of the Customer, sales effectiveness depends mightily on the buyer experience. Despite the wealth of research documenting the need for creating value in every step of the buyers journey, sellers continue to struggle with how to create that value and connect meaningfully with buyers. New research with 530 B2B buyers in a 2016 Qualtrics Panel Study reveals the 30 behaviors that would cause buyers to be more likely to meet with sellers and more likely to buy from them. Buyers preferences are for behaviors that are more often associated with leadership than with sales. This suggests a critical shift in the selling mindset and in the sales role itself is needed, in addition to a behavioral shift, for organizations that want to boost overall sales effectiveness."--